Lower pregnancy rate in women with high uterine peristalsis before embryo transfer: a systematic review and meta-analysis - Angela Vidal; Valeria Trejos; Janna Pape; Tanya Karrer; Gürkan Yilmaz; Michael von Wolff (Reproductive Biology and Endocrinology)
Abstract Background Uterine contractions, also known as peristalsis, have been shown to affect fertility. However, despite previous studies, most clinicians have not paid sufficient attention to uterine peristalsis. Recent studies have recognised its importance and evaluated contractility parameters prior to embryo transfer. Method A systematic literature search was conducted in Medline, Embase and Cochrane CENTRAL up to January 2024. Inclusion criteria were studies involving patients undergoing in vitro fertilization (IVF) or other infertility treatments in which uterine contractility was assessed. Studies were excluded if they included therapeutic interventions that affected contractility, or if they focused on uterine pathologies such as adenomyosis or fibroids. The meta-analysis included trials with IVF treatments that compared clinical pregnancy rates in women with high versus low frequent uterine contractions. Results A total of 2587 women (17 studies) were included in the systematic review, of whom 1134 (43.1%) (5 studies) underwent embryo transfer and were eligible for meta-analysis. The review found that elevated contractility on the day of embryo transfer is associated with a negative impact on pregnancy rates. The meta-analysis showed that women with two or more uterine contractions at the time of the embryo transfer had a significantly lower clinical pregnancy rate than with women with two or fewer contractions (OR 0.52, 95% CI: 0.38- 0.69). There was moderate heterogeneity between studies (I2 = 55, p < 0.01). Conclusions The lower clinical pregnancy rate in women with high uterine contractility, highlights the role of uterine peristalsis around the time of embryo implantation. However, due to the limited and heterogeneous data available, the influence of uterine peristalsis on reproductive outcomes such as live birth rates remains unclear.